Evaluation of superabsorbent linseed-polysaccharides as a novel stimuli-responsive oral sustained release drug delivery system. (4th March 2017) - Haseeb, Muhammad Tahir; Hussain, Muhammad Ajaz; Bashir, Sajid; Ashraf, Muhammad Umer; Ahmad, Naveed
Abstract: Context: Advancement in technology has transformed the conventional dosage forms to intelligent drug delivery systems. Such systems are helpful for targeted and efficient drug delivery with minimum side effects. Drug release from these systems is governed and controlled by external stimuli (pH, enzymes, ions, glucose, etc.). Polymeric biomaterial having stimuli-responsive properties has opened a new area in drug delivery approach. Objective: Potential of a polysaccharide (rhamnogalacturonan)-based hydrogel from Linseeds ( Linum usitatissimum L.) was investigated as an intelligent drug delivery material. Materials and methods: Different concentrations of Linseed hydrogel (LSH) were used to prepare caffeine and diacerein tablets and further investigated for pH and salt solution-responsive swelling, pH-dependent drug release, and release kinetics. Morphology of tablets was observed using SEM. Results: LSH tablets exhibited dynamic swelling–deswelling behavior with tendency to swell at pH 7.4 and in deionized water while deswell at pH 1.2, in normal saline and ethanol. Consequently, pH controlled release of the drugs was observed from tablets with lower release (<10%) at pH 1.2 and higher release at pH 6.8 and 7.4. SEM showed elongated channels in swollen then freeze-dried tablets. Discussion: The drug release was greatly influenced by the amount of LSH in the tablets. Drug release from LSH tablets was governed by the non-Fickian diffusion. Conclusions: These finding indicates that LSH holds potential to be developed as sustained release material for tablet.